Whey protein: The “whey” forward for treatment of type 2 diabetes? - Mignone, Linda E (World J Diabetes, 2015)
A cost-effective nutritional approach to improve postprandial glycaemia is attractive considering the rising burden of diabetes throughout the world. Whey protein, a by-product of the cheese-making process, can be used to manipulate gut function in order to slow gastric emptying and stimulate incretin hormone secretion, thereby attenuating postprandial glycaemic excursions. The function of the gastrointestinal tract plays a pivotal role in glucose homeostasis, particularly during the postprandial period, and this review will discuss the mechanisms by which whey protein slows gastric emptying and stimulates release of gut peptides, including the incretins. Whey protein is also a rich source of amino acids, and these can directly stimulate beta cells to secrete insulin, which contributes to the reduction in postprandial glycaemia. Appetite is suppressed with consumption of whey, due to its effects on the gut-brain axis and the hypothalamus. These properties of whey protein suggest its potential in the management of type 2 diabetes. However, the optimal dose and timing of whey protein ingestion are yet to be defined, and studies are required to examine the long-term benefits of whey consumption for overall glycaemic control.